Semantic Reconstruction of Inverse Immigration by Grounded Theory: Case of Divandarreh District, Iran - Ghodrati, Hossein; Salimi, Kaveh; Ghodrati, Shafieh (International Journal of Agricultural Management and Development, 2025)
Migration, as an integral component of both regional and international processes, significantly impacts the contemporary world and the spatial mobility of societies, influencing family, social bonds, economy, politics, culture, and communication. This research aimed to examine the social reconstruction of reverse migration based on the interpretations and mental meanings of those who have experienced it. Grounded theory and semi-structured interviews were used for this purpose. The participants included 16 individuals who had returned as migrants from the city of Saqez to the village of Abbareh in Iran. These individuals were selected through theoretical sampling and the criterion of theoretical saturation. The data were coded into 145 concepts, 15 major categories, and 1 core category encompassing the axial category. The categories include: economic advantages of the village over the city, unfavorable social conditions in the city, favorable social conditions in the village, unfavorable psychological states in the city, favorable psychological states in the village, facilitated communication, rural attractions, improved village services, attachment to village nature and community, physical incompatibility with the city, emphasis on consuming local products, increased potential and changing attitudes, new rural repulsions, trust and intimacy, and the factor of migration to the city. These categories are presented in a paradigmatic model based on three dimensions: causation, strategies, and outcomes. Ultimately, the core category identified was "perceived relative advantage of the village." The findings indicate that reverse migration resulted from the perceived social, economic, and leisure benefits of village life compared to the city. The return of migrants was driven by dissatisfaction with urban living and the presence of job opportunities, leisure attractions, intimacy, and trust among friends, relatives, and village residents.